Fiction and National Consciousness in Ngozi Chuma-Udeh’s Teachers on Strike - Ogbazi, Ifeyinwa; Ofie, Chukwuka Eugene (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This research work focused on fiction and national consciousness in Ngozi Chuma-Udeh’sTeachers on Strike. Teachers on Strike by Ngozi Chuma-Udeh provides the anchor for the evaluation of societal malaise in the novel. Much of the critical study of Post-Independence Nigerian Literature is mainly on disillusionment. It is the emergent literary tradition highlighting the interface of literature and resistance in Nigerian novels that this study focuses on, it attempts to advocate resistance as means of effecting change in society. The study employs the content analysis approach to qualitative research. The theoretical framework is Marxism and sociological approach to literature. These theories advocate literature as weapon against negative forces militating against the people as well as proffering ways in which the society can be redeemed from man-made atrocities. This study ultimately broadens literary scholarship on resistance discourse in Nigerian novels.